Numerical quantum dynamics - Schweizer, Wolfgang (Kluwer Academic, 2015)
Computational quantum dynamics involves the use of computer calculations and simulations to solve quantum physical problems. This text describes computational methods used in quantum dynamics with emphasis on small quantum systems.